Sex, Receptors, and Attachment: A Review of Individual Factors Influencing Response to Oxytocin - Macdonald, Kai S. (Frontiers in Neuroscience, 2013)
As discussed in the larger review in this special issue (MacDonald and Feifel), intranasal oxytocin (IN OT) is demonstrating a growing potential as a therapeutic agent in psychiatry. Importantly, research suggests that a variety of individual factors may influence a person’s response to OT. In this mini-review, I provides a review of three: (1) sex and hormonal status; (2) genetic variation in aspects of the OT system (i.e. OT receptors); and (3) attachment history. Each of these factors will be important to monitor as we strive to develop a richer understanding of OT's role in human development, brain-based disease, and the potential for individualized, OT-targeted treatments.